Semi-active vehicle suspension using smart fluid dampers: a modelling and control study. (23rd February 2004) - Sims, N.D.; Stanway, R.
In this paper, the authors present a numerical investigation of semi-active vehicle suspensions based upon smart fluid dampers. After demonstrating the unsuitability of employing a smart damper in open loop, the advantages of linearising the force/velocity response are demonstrated. It is shown how a smart damper with force feedback can operate as a controllable viscous damper. Skyhook systems based upon smart dampers are investigated and shown to offer significant performance gains over conventional passive systems. The above work was performed essentially using validated models of ER dampers. However, a study of the likely slower response of MR dampers suggests that the speed of response should not prove an obstacle to the successful application of MR-based semi-active suspensions.